2018
DOI: 10.1111/jace.15548
|View full text |Cite
|
Sign up to set email alerts
|

Use of nanocomposites as permeability reducing admixtures

Abstract: Permeability is one of the fundamental properties of concrete structures as it is strictly related to durability. Mitigation of the degradation processes induced by aggressive solutions can be achieved by controlling water penetration through the pore network. In this study, we test the potential use of nanocomposites as waterproofing agents in concrete. Macroscopic measurements show that the addition of a small amount of nanoparticles effectively reduces the extent of the water permeation front. A combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The final suspension, of light blue color, had a total solid content of 23 wt.% and a viscosity of 0.12 N·s·m −2 , measured at 20 °C. Previous sample characterization certifies the effective synthesis of nano-sized particles of a few tens of nanometers in diameter [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final suspension, of light blue color, had a total solid content of 23 wt.% and a viscosity of 0.12 N·s·m −2 , measured at 20 °C. Previous sample characterization certifies the effective synthesis of nano-sized particles of a few tens of nanometers in diameter [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the hydration process is regulated by a high number of parameters that influence the dissolution/precipitation kinetics of several phases in the aqueous environment [ 1 ]. Moreover, the particle size, the modulation of water-to-cement ratio and the use of chemical admixtures to modify the particle dispersion and the kinetics of the reaction during hydration directly influence the workability of the binder as well as the strength development and the microstructure of the hardened material [ 1 , 2 , 3 , 4 ]. The system complexity further increases when OPC is partially replaced by supplementary cementitious materials (SCMs), both as naturally occurring materials or as industrial by-products that take part in the pozzolanic reactions, or by formulating alternative OPC-free binders as the alkali-activated materials (AAMs) [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the good mechanical strength (and durability) performances at 28 days or later, synchrotron X-ray diffraction tomography showed that C-S-H addition partly moves away the gel nucleation and growth from the dissolving clinker particles, enhancing secondary nucleation in the capillary porosity of the paste [ 42 ]. The shift of the C-S-H gel from the surfaces of alite to the pore space leads to a more homogeneous distribution of C-S-H products in the bulk of the paste [ 38 ], which in turn may reduce the porosities, improving the mechanical strength properties and decreasing the permeability of the final binder [ 43 ]. Concerning the early age acceleration of cement hydration, it was proposed [ 21 ] that alite hydration is accelerated because the synthetic C-S-H seeds provide additional nucleation sites, enabling the C-S-H from alite to rapidly grow.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer nanocomposites have outweighing advantages in comparison with using nanomaterials as nanocomposites being controlled and stabilized dispersion of nanomaterials in the polymer matrix. , There have been several propositions where nanomaterials are used to enhance the properties of cement slurry. , Apart from maintaining an adequate compressive strength, the nanomaterials maintain a requisite fluid level in the cement slurry, retain the slurry performance properties in the desirable range, and demonstrate better thermal stability than is seen in other nanocomposites. , Ghosal et al discussed in their study that the incorporation of polymeric nanocomposite in the cement slurry has the potential to enhance the mechanical properties of cement slurry . Valentini et al, in their study, concluded that the addition of 3–5% of nanocomposites can alter the pore network to restructure in finer sizes to help in permeability reduction for better sealing performance . Karapinar et al found that the application of a small percentage of nanocomposites in the cement increases the compressive strength by 10–11% …”
Section: Introductionmentioning
confidence: 99%